A discrete wavelet transform and fuzzy logic algorithm for identifying the location of fault in underground distribution system - Bunjongjit, S.; Ngaopitakkul, A.; Pothisarn, C. (My University, 2013)
This paper proposes the hybrid decision algorithm of discrete wavelet transform (DWT) and fuzzy logic in order to identify the location of fault in underground distribution cable. The high frequency component obtained from DWT with the mother wavelet daubechies4 (db4) is used as an index for the occurrence of faults. The first peak time of DWT, obtained from positive sequence that can detected the occurrence of faults are considered as an input pattern of decision algorithm. The obtained average accuracy results have shown that the proposed decision algorithm is able to identify the location of fault with satisfactory accuracy. © 2013 IEEE.
Keywords: Discrete Wavelet Transform; Fault Location; Fuzzy Logic; Underground Distribution System